Development of Business Strategy For Doping Studio - Harimurti, Krisna; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract. In Indonesia, children play an important role in product purchasing and preference of a family which consist of 70% of total family expenditure be spent for children needs and wants. This clearly indicates the potential and uniqueness of children market where their purchasing power comes from their parents. Therefore, children party planner business in Indonesia is a promising opportunities business that aims to help parents, which are time and fund constraint, in organizing memorable and emotionally attached moments with their children. Kiddy-O is a start-up company that position itself as Personalized Party Planner for Children which existed by specifically targeting niche market that includes events, party, and gathering where its main target customer object is children below 12 years old. Every start-up business faced high challenges in competing for success especially those in preliminary stages. This issue is also faced by Kiddy-O. This study therefore aim to find out the appropriate STP strategy and the targeted market audience needs in party planner of children service for the prospect of Kiddy-O business. Kiddy-O have to understand their target market rigorously and understanding the demands in order to provide product and services that are able to fulfil the demand of the market. It is essential for Kiddy-O to overcome this issue since it will help Kiddy-O during early stages and prevent from insolvency. Moreover, by understanding their target market well, Kiddy-O will be able to compete and survive in this business industry. To complete the analysis of the internal and external terms, the method of analysis used questionnaires to determine the views of consumers need of party planner for kids. Questionnaire addressed to 40 female respondents who live or work in Bandung City and have children age under 12 years old. After that, the survey result use to create strategy formulation, the author try to match Segmenting, Targeting and Positioning analysis based on author assumption and survey result of questionnaire. Kiddy-O’s consumers segment are female with range of below 25 – 45 years old above. Their last educational level are high school, diploma, bachelor and master. Segmentation by occupation is employees, entrepreneur and housewife. With average income between Rp 2,500,000 – Rp 7,500,000 above per month. And the geographic aspect divided into Bandung, West Java, Indonesia. Consumers social class are from upper class and consumers life style are divided into conspicuous consumers and survivor. Segmentation market is educated well. And the attitude are hardworking, acquisitive and competitive, concerned with position and show. Kiddy-O target market are female with range of 25 until 35 years old, have children age under 12 years old, bachelor degree, work as employees with the average income Rp 5,000,100 – Rp 7,500,000 live in Bandung. Positioning, the concept that were offered by Kiddy-O is to become a personalized private party planner that provide an interactive thematic events. To re-enacted traditional fun games and songs as well to promote Indonesian culture with fresh new ideas and concept by integrating an interactive activity games and challenges. Based on the research, there are many demand in this service. They think that using Party Planner service is important. Many of them will use this service for arrange birthday party events, despite will use the service for celebrate circumcision is becomes potential market too. Consumers satisfaction becomes the main objective. If the events not as good as expected, Kiddy-O will give compensasion to minimize complaints from consumers. We will do preventive action and make sure it does not happen again. Because the quality control and customer satisfaction are the important indicators that can make survive in business.Key Words: Party Planner, Children, Segmenting, Targeting, Positioning